Pengaruh Pelatihan Dan Kompesasi Terhadap Kinerja Karyawan Saung Ranggon Kota Tasikmalaya - Rahmania, Anissa; Sudono, Agus; Ridwanudin, Oce (Universitas Pendidikan Indonesia, 2016)
The rapid development of restaurants business, especially in the town ofTasikmalaya, less accompanied by a good performance of the employees. One of them is in Saung Ranggon, Tasikmalaya. Those were noticed by the indicator of employees’who are less knowledge in handling the consumer, time spent by consumer waiting for their order, and employees presence level are graded less good. These phenomenons must be solved immediately in order not to interfere the company’s performance. A routine given training and fixing compensating system are a few of the methods to increase employees’ performance so that the company’s target can be achieved.The purpose of this research is to acknowledge the description of: (1) Trainingin Saung Ranggon Tasikmalaya City; (2) Compensating in Saung RanggonTasikmalaya City; (3) Employees’ performance in Saung Ranggon Tasikmalaya City, and to know the effect of: (4) Training in Saung Ranggon Tasikmalaya City, (5) Compensating in Saung Ranggon Tasikmalaya City; (6) Trainingand compensating toward employee’s performance in Saung Ranggon, Tasikmalaya City. Object of this research is employees of Saung Ranggon Tasikmalaya City. Independent variable in this research is the training and compensating, whilst the dependent variable is employees’ performance. This research use descriptive and verificative approach. Applied method in this research is explanatory survey with population of 38 individuals (saturated sample). Data Analysis technique which is used in this study is multiple linear regression by using SPSS 22.0. In this research stated that: (1) Training in Saung Ranggon Tasikmalaya City were on high category; (2) Compensating in Saung Ranggon Tasikmalaya City were on high category; (3) Employees’ performance in Saung Ranggon Tasikmalaya City were on high category; (4) Training in Saung Ranggon Tasikmalaya City gives positive effect on employees’ performance with the corellation level of 29,1%; (5) Compensating Saung Ranggon Tasikmalaya City gives positive effect on employees’ performance with the corellation level of 51,6%; (6) Training and Compensating in Saung Ranggon Tasikmalaya City gives positive effect on employees’ performancewith the corellation level of 59,4%.. Author’s suggestion is that Saung Ranggoncan conduct such training to the employees sustainably and pay attention toemployees’ welfare.